Application of Electrical Technology Using Website as a Digital Communication Science Media Based on Information and Communication Technology at Amari Teaching and Learning Centre - Setiyo Budiyanto; Irmulansati Tomohardjo; Fauzi Nur Iman; Lukman Medriavin Silalahi (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2024)
Amari Teaching and Learning Centre (TLC), the community partnership empowerment program partner is located in South Meruya, West of Jakarta, which is active in the field of education in the form of A-package (elementary school education level) to C-package (high school education level). The number of teachers and educators is 8 persons and the current students have reached 101 male students and 43 female students. The problem experienced by the partners was that they did not have a website as a promotional medium. Thus, by integrating expertise and experience in organizational management and information and communication technology, targets were set, namely for: a) website development, b) training of teaching staff and administration staff, c) integration of technology in learning activities, d) strengthening website management capacity, e) strengthening partnerships and networks, and f) continuous monitoring and evaluation. The output is an increase in the understanding and skills of Amari TLC managers.